Neuroglobin is an endogenous neuroprotectant for retinal ganglion cells against glaucomatous damage - Wei, Xin; Yu, Zhanyang; Cho, Kin-Sang; Chen, Huihui; Malik, Muhammad Taimur A; Chen, Xiaoming; Lo, Eng H; Wang, Xiaoying; Chen, Dong F (The American journal of pathology, 2011)
Neuroglobin (NGB), a newly discovered member of the globin superfamily, may regulate neuronal survival under hypoxia or oxidative stress. Although NGB is greatly expressed in retinal neurons, the biological functions of NGB in retinal diseases remain largely unknown. We investigated the role of NGB in an experimental model of glaucoma, a neurodegenerative disorder that usually involves elevation of intraocular pressure (IOP). Elevated IOP is thought to induce oxidative stress in retinal ganglion cells (RGCs), thereby causing RGC death and, eventually, blindness. We found that NGB plays a critical role in increasing RGC resistance to ocular hypertension and glaucomatous damage. Elevation of IOP stimulated a transient up-regulation of endogenous NGB in RGCs. Constitutive overexpression of NGB in transgenic mice prevented RGC damage induced by glutamate cytotoxicity in vitro and/or by chronic IOP elevation in vivo. Moreover, overexpression of NGB attenuated ocular hypertension-induced superoxide production and the associated decrease in ATP levels in mice, suggesting that NGB acts as an endogenous neuroprotectant to reduce oxidative stress and improve mitochondrial function, thereby promoting RGC survival. Thus, NGB may modulate RGC susceptibility to glaucomatous neural damage. Manipulating the expression and bioactivity of NGB may represent a novel therapeutic strategy for glaucoma.